MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA DUKUH, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Anwar, Miftakhul; Yanti, Novi (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2025)
This community service aims to design an optimal and appropriate LKMS model for village communities by considering social and economic factors and compliance with sharia values. This community service was carried out in Dukuh Village, Cibungbulang District, Bogor Regency, West Java Province. This community service uses Participatory Action Research (PAR). Dukuh Village is a fertile area for agriculture. Its area is divided into Rice Fields, Dry Land, Wet Land, Plantations, Public Facilities, and Forests with a total of 162.32 Ha. The majority of residents have commercial shops, especially small household needs shops. The main sectors in Dukuh Village are agriculture and animal husbandry. For innovation, they utilize horticultural agricultural products such as spinach for BOBOYUR or Boba vegetables. Entrepreneurs here often have difficulty applying for bank loans due to lack of knowledge about sharia banking. Therefore, it is important to provide information and education to the people of Dukuh Village about applying for sharia bank loans. The result of this activity is that the community is equipped with knowledge about Islamic Microfinance Institutions and also various financing in it. The introduction of Islamic Microfinance Institutions and Microfinance can reduce the community in financing using usury and can improve the quality of Islamic Microfinance Institutions and Microfinance